Internal Medicine Nurses' Perceptions of Work Environment Ergonomics and Safety Climate. - Aktepe Coşar, Dilan; Demirağ, Hatice; Nashwan, Abdulqadir J. (Perspectives in Psychiatric Care, 2025)
Objective: This study aimed to examine the relationship between the ergonomic conditions of the work environment and the perception of safety climate among internal medicine nurses. Materials and Methods: This descriptive study was conducted between October 30, 2023, and January 30, 2024, with a total of 440 internal medicine nurses in Turkey using the "snowball sampling" method. Data were collected using the "Personal Information Form," the "Workplace Ergonomics Scale for Nurses," and the "Safety Climate Scale." Results: A statistically significant difference was found in the mean scores of the "Workplace Ergonomics Scale for Nurses" based on marital status, educational level, perceived workload, and whether the nurses had received occupational safety training (p < 0.05). However, no significant difference was observed in the scale scores based on gender, professional experience, or satisfaction with the work environment (p > 0.05). A significant difference was also identified in the mean scores of the "Safety Climate Scale" according to gender, educational level, professional experience, satisfaction with the work environment, and occupational safety training status (p < 0.05). A significant negative correlation was found between the scores of the "Workplace Ergonomics Scale for Nurses" and its subdimensions and the safety training subdimension scores. Data were analyzed using t‐test, ANOVA, and correlation analysis. Conclusion: In conclusion, improving ergonomic conditions, strengthening managerial support, establishing effective safety communication, and promoting continuous education are recommended as key strategies to ensure that nurses work in a safe and supportive environment. Additionally, implementing tailored interventions based on demographic and professional characteristics may contribute to the development of a safety culture in nursing and the improvement of patient care quality.